Field notes contributed by Carl J. Bendorf, fall 1984 - Bendorf, Carl J.et al (1984)
Field notes were contributed by Carl J. Bendorf, fall 1984. He sighted 40 species with three other observers. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of fall 1984. Epson - sheet feed